(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2019)
This paper brings to light optimized proposal for a circular particle accelerator for proton beam therapy purposes (named as ACPT). The methodology applied is based on computational metaheuristics based on genetic algorithms (GA) were used to obtain optimized parameters of the equipment. Some fundamental concepts in the metaheuristics developed in Matlab® software will be presented. Four parameters were considered for the proposed modeling for the equipment, being: potential difference, magnetic field, length and radius of the resonant cavity. As result, this article showed optimized parameters for two ACPT, one of them used for ocular radiation therapy, as well some parameters that will allow teletherapy, called in order ACPT – 65 and ACPT – 250, obtained through metaheuristics based in GA.